The effects of high strain-rate and temperature on tensile properties of UHMWPE composite laminates - Alia Ruzanna Aziz; Haleimah Al Abdouli; Naresh Kakur; Henrique Ramos; Rafael Savioli; Zhongwei Guan; Rafael Santiago (Composites Part C: Open Access)
The high strain-rate and temperature properties of ultra-high molecular weight polyethylene (UHMWPE) composites are limitedly available in the public domain, primarily due to challenges in gripping the extremely strong material during testing. In this study, tensile tests were performed on UHMWPE laminates over a range of strain-rates from 4.00 × 10-4 to 2.45 × 102 s-1, and at different temperatures from -10 to 70 °C using an innovative interchangeable clamping system. The clamp was designed to overcome gripping issues while ensuring consistent boundary conditions across various testing devices. Digital Image Correlation (DIC) technique was employed to capture the displacement fields in situ. The results show that UHMWPE composites demonstrate strain-rate strengthening and temperature-induced softening effects. The strain-rate dependent models indicate a notable difference in strain-rate sensitivity, particularly with tensile strength exhibiting 87 % and 60 % higher sensitivity compared to the tensile modulus and failure strain, respectively. The Weibull statistical model indicates that the scale parameter increases by 17 % with the increase in strain-rate due to transition in failure response from ductile to brittle, which is observed through optical microscopy. In contrast, the scale parameter decreases by 58 % with the increase in temperature. Therefore, it is important to consider the effects of strain-rate and temperature on the mechanical properties for effectively utilizing this material to develop numerical models in various impact-protective applications.